IMPLEMENTASI TEKNOLOGI LORA DAN NODEMCU ESP8266 PADA ALAT EARLY WARNING SYSTEM UNTUK PEMANTAUAN KUALITAS UDARA - Fiqqih Faizah; Kustori; I W.Y.M. Wiguna; Suhanto; A. Abdullah (Jurnal Penelitian)
Good air quality is important for the health and comfort of the people living in that environment. Air quality conditions at a location can be determined from the levels of pollutants and harmful gases. The most easily known air quality parameters are temperature, humidity, and levels of harmful gases present. This research presents an air quality monitoring instrument that utilizes Long Range (LoRa) wireless technology for data transmission. This tool consists of a sensor node section that functions to detect air quality in a certain area, as well as a gateway section that functions to receive data from the sensor node to be forwarded to the operator. Each set of sections is equipped with a LoRa SX1276 module that works at a frequency of 915 MHz for data communication and NodeMCU ESP8266 for data processing. The sensor node is equipped with a DHT22 sensor to detect temperature and humidity and an MQ7 sensor to detect carbon monoxide (CO) levels. The reading results of these sensors are forwarded by the sensor node to the gateway to be displayed on a 0.96” OLED. The gateway is also equipped with a buzzer that will sound if a temperature reading value exceeds 40 oC is found, humidity does not meet the 45-65% RH range, and CO levels exceed 12 ppm. The test results showed that the buzzer function can work properly according to the specified sensor reading value and the maximum distance between the sensor node and the gateway for optimal data communication is a radius of 400 m when tested at the Politeknik Penerbangan Surabaya.